ChemInform Abstract: Bimetallic Dendrimer‐Encapsulated Nanoparticle Catalysts. Issue 40 (16th September 2016) - Wang, Hui; Rempel, Garry L.
Abstract: Review: recent research advances in the synthesis, characterization, and catalytic proerties; 90 refs.